Література еміграції. Художній досвід існування історичної прози в обшарі чужої культури - Набитович, І. (Слово і Час, 2022)
У статті на прикладі історичної прози розглянуто особливості існування літератури української еміграції. Продемонстровано основні тенденції розвитку, теми й мотиви цього конкретного жанрового утворення.
Задекларовано, що для суспільств, у яких була перервана державницька
традиція, історична епіка може виступати важливим чинником відновлення / утримування національної пам’яті, а також — засобом творення національних мітів, проєктування минулого на сучасні проблеми
бездержавної нації, консервації національних традицій. Історичне письменство взяло на себе відповідальність за націософську перспективу, закорінену в минуле, — для збереження і примноження її в майбутньому. Historical novel, as a special genre formation born of Romanticism, has become an artistic
tool for the reproduction of the past, its discovery and invention. Historical prose is the
literary space where two worldview narrative strategies intersect, overlap, and sometimes
collide: these are history that (in its academic sense) seeks to recreate the ‘true past’, and
literature, which is a particular representation and development of the world.
Historical prose of Ukrainian emigration appears as a fairly integral literary and aesthetic
phenomenon during two interwar decades of the 20th century and ends at the border of the
1990s — after Ukraine gained its independence.
For nations that lost their statehood, the return of the past, its glorification is an
important means of forming national identity and self-consciousness. The historical novel of
the Ukrainian emigration is a relentless attempt to root its next generations in the national
tradition of collective memory.
In general, for societies in which the state tradition has been interrupted, historical
prose can be an essential factor in restoring / maintaining national memory, as well as a
means of creating national myths, projecting the past into modern problems of a stateless
nation, and preserving national traditions. The historical prose of the Ukrainian emigration
was actually focused on these aims, taking responsibility for the nationalist and philosophic
perspective rooted in the past in order to preserve and increase it in the future.
The aspiration and experience of Ukrainian emigration in other countries carries a
number of tasks that it set for itself. These were, in particular, the preservation of the native
language, culture, and creative activity, including historical prose on the themes prohibited
in the mainland literature, the formation of the strategy of collective memory through
historical prose.